1986
DOI: 10.1252/jcej.19.111
|View full text |Cite
|
Sign up to set email alerts
|

Fed-batch culture of Escherichia coli harboring a runaway-replication plasmid.

Abstract: CultureIn fed-batch cultivation of Escherichia coli harboring a runaway-replication plasmid pCP3, runaway replication could not be induced at all by shifting the cultivation temperature from 30 to 42°C, which has normally been used in small-scale experiments. Therefore, cultivation conditions were reexamined by shake-flask cultivations. It was found that the plasmid copy number was restricted to a low level at 25°C but increased gradually at 30°C, and that full runaway replication could be induced at 37°C. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In particular, we expected greater copy number control before the temperature shift; however, we are not the first group to observe that runaway replication is not completely suppressed at 30°C [14,19]. To further investigate the temperature-dependent behavior of pDMB02-GFP we pursued additional studies at the RNA and protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we expected greater copy number control before the temperature shift; however, we are not the first group to observe that runaway replication is not completely suppressed at 30°C [14,19]. To further investigate the temperature-dependent behavior of pDMB02-GFP we pursued additional studies at the RNA and protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve these problems, we studied the culture conditions of Escherichia coli containing recombinant plasmids such as a runaway replication plasmid (Mizutani et al 1986a(Mizutani et al , 1987a, trp (Kawai et al 1986) and pho promoterbearing ones. Among them, the gene expression from the trp orpho promoter could be derepressed by either tryptophan or phosphate starving in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the gene product encoded by runaway-replication plasmid increases exponentially by induction [2]. Thus, a mathematical model describing both the response of a runaway replication to temperature shift and the cultivation characteristics of the recombinant E. coli is proposed as follows.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…We observed that the gene product increased exponentially in the logarithmic growth phase [2]. For simplicity, we assumed that nutrients, such as carbon source, are well controlled and that their effects on the specific growth rate were negligible.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation